Modelo de Ohlson y la proyección de la estabilidad en las microempresas del sector constructor de la ciudad de Riobamba, período 2020-2022 - Medina Rivera, Lady Abigail (2024)
ABSTRACT: The microenterprises of the construction sector in Ecuador have become an important sector, promoting the socioeconomic development of the citizenship, therefore it is important to know the financial and economic situation of these entities to remain in the market, for this reason this research aimed to apply the Ohlson model to project the financial and economic stability in microenterprises of the construction sector in the city of Riobamba, period 2020-2022. The research methodology is deductive with a quantitative approach based on a non-experimental design of exploratory and documentary type. We worked with a population of 18 microenterprises in the construction sector. Through the techniques of documentary analysis and indirect observation, with the instruments of the risk matrix and the indirect observation guide, information was collected from the financial statements and results corresponding to the year 2020, 2021 and 2022 from the portal of the Superintendence of Securities and Insurance Companies for the application of Ohlson's O1, O2 and O3 model and the liquidity, solvency and profitability indicators. As a result, the instability of 7 micro-companies was projected using the O3 model, the instability of 11 construction companies was projected using the O2 model, and 4 micro-companies were projected to be unstable using the O1 model. When applying the liquidity indicators, it was determined that the entities can cover their obligations with third parties, the indebtedness of the microenterprises is relatively low, while the level of profitability of most of the microenterprises does not exceed 1% profitability in their operational activities. Key words: Stability, microenterprises, construction sector, Ohlson model, liquidity, profitability, solvency